2012
DOI: 10.3945/ajcn.112.035253
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with B vitamins or n−3 fatty acids and depressive symptoms in cardiovascular disease survivors: ancillary findings from the SUpplementation with FOLate, vitamins B-6 and B-12 and/or OMega-3 fatty acids (SU.FOL.OM3) randomized trial

Abstract: We showed no beneficial effects of a long-term, low-dose supplementation with B vitamins or n-3 fatty acids on depressive symptoms in cardiovascular disease survivors. The adverse effects of n-3 fatty acids in men merit confirmation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 33 publications
0
46
0
1
Order By: Relevance
“…Hence, this latter has been translated in a correlation of efficacy to more severe symptoms whereas, according to our results, we hypothesized that this efficacy may be more related to the specific pathophysiological processes of the MDD rather than to its severity. Compared with previous meta-analyses, the differences of findings may depend on the additional number of RCTs published since the publication of the last study [37], [40], [53], [60], [61], [66], [68], [69], [84], [89], [92], [94][97], [100][102], the increasing number of participants which vary the overall weight of previous studies, the requirement for public registration of trials resulting in an increase of general studies’ quality and may be responsible for the decreased evidence of publication bias.…”
Section: Discussionmentioning
confidence: 83%
“…Hence, this latter has been translated in a correlation of efficacy to more severe symptoms whereas, according to our results, we hypothesized that this efficacy may be more related to the specific pathophysiological processes of the MDD rather than to its severity. Compared with previous meta-analyses, the differences of findings may depend on the additional number of RCTs published since the publication of the last study [37], [40], [53], [60], [61], [66], [68], [69], [84], [89], [92], [94][97], [100][102], the increasing number of participants which vary the overall weight of previous studies, the requirement for public registration of trials resulting in an increase of general studies’ quality and may be responsible for the decreased evidence of publication bias.…”
Section: Discussionmentioning
confidence: 83%
“…289 Conversely, COX and LOX metabolites of ω-6 FFA such as arachidonic acid (e.g., prostaglandin E 2 and thromboxane) are often pro-inflammatory 282, 290, 291 Notably, ω-3 FFA supplementation could specifically be for ICAD, as it does not prevent post-partum depression 292 nor perinatal depression, 293 nor vascular depression. 294 Thus, both sleep and ω-3 FFA may be good clinical targets for preventing ICAD.…”
mentioning
confidence: 99%
“…In the VITATOPS study, treatment with B vitamins ranging from one to 10.5 years (mean 7.2 years) reduced the risk of a major depressive episode [32]. Conversely, the SU.FOL.OM3 trial found no effects of B vitamin supplementation on depressive symptoms in those with a cardiovascular disease history [65]. Interestingly, supplementation with omega 3s in men resulted in a 28% higher risk of presenting with depressive symptoms than those receiving a placebo, with no such increased risk observed in women.…”
Section: Subjective Outcomesmentioning
confidence: 99%